(untitled) (Medina-Te : Jurnal Studi Islam, 2017)
The existence of Nucleic Acid Tests Deoxyribo in determining nasab, this revealed about practical of DNA tests of proving their nasab relationship. Issues as was seen from the perspective of the Positive Law and Islamic Law which will look Existence of Deoxyribo Nucleic Acid Tests to determine nasab both in the perspective of Positive Law and Islamic Law. The purpose of Deoxyribo Nucleic Acid Test was to determine the legal certainty the results of DNA testing as evidence to determine nasab in view of the Positive Law and to analyze Islamic Law Review toward the existence of a DNA testing to determine nasab. DNA testing in the Positive Law could be used as valid evidence that as a subsidiary or additional evidence in addition must be supported by other evidence, as if linked in determining nasab particularly children that born outside of marriage it did not have the force of law and legal certainty. So both in Law No. 1 of 1974 and the Islamic Law Compilation that DNA testing was not regulated either as evidence or not, because basically in the Civil Code, Criminal Code and the Law on Children Protection also had been no the evidence type of DNA testing. Further DNA testing in the context of Islamic law could be used as legal evidence, but needed to be seen from his goal, because DNA testing also could not be separated from Maqasid as-shar 'iah namely giving the benefits while keeping human existence in nature needs of ḍaruriyyât and if the purpose of the DNA testing that deviated from the provisions of Islamic law, the existence prohibited. Proof through DNA testing could be categorized as evidence of qarinah whose authenticity was quite accurate, so no longer in doubt.